The Social and Economic Structure of the Axylon Region in the Light of Grave Steles in the Ancient Period - Kurt, Mehmet (Fırat University, 2024)
In antiquity, the northern Lycaonian steppes from west of Tatta Limn? (Salt Lake) to north of Laodikeia (Konya-Ladik) were called Axylon. The region, which is evaluated in different sections as East, Southeast and West due to the changes in the land structure from place to place, covers the districts of Kadınhanı, Sarayönü, Cihanbeyli and partially Kulu in today's Konya province.Axylon means treeless country and the eastern part of Axylon is also called Proseilemmene.As is the case presently, the primary means of sustenance in this area during ancient times was agriculture and raising animals.Ancient texts do not provide a comprehensive view of the region's social and economic status. However, the depictions on the grave steles obtained from the settlements in the region called Axylon in Ancient Period clearly reveal that the people of the region were engaged in farming. Indeed, a majority of the embellishments, particularly on the tomb stelae, connect with agrarian practices. Throughout the region, ploughing scenes, plows, yokes, wheat ears, vine leaves, grape bunches, wool baskets, and spindles are frequently seen figures. This study discusses the social and economic life of the region in Antiquity on the basis of written sources and in particular the depictions on the grave steles.

Antik Dönemde Tatta Limn?’nin (Tuz Gölü) batısından Laodikeia’nın (Konya-Ladik) kuzeyine kadarolan Kuzey Lykaonia bozkırlarına Axylon denilmekteydi. Arazi yapısının yer yer değişiklik göstermesinden kaynaklı olarak Doğu, Güneydoğu ve Batı olmak üzere farklı bölümler halinde değerlendirilen bölge, günümüzdeki Konya ili Kadınhanı, Sarayönü, Cihanbeyli ve kısmen Kulu ilçelerini kapsamaktadır. Axylon, ağaçsız ülke anlamına gelmekte olup, Axylon’un Doğu kesimi,Proseilemmene olarak da adlandırılmıştır. Bugün olduğu gibi Antik Dönemde de bölgenin temel geçim kaynağını tarım ve hayvancılık oluşturmuştur. Antik edebi kaynaklar bölgenin sosyal ve ekonomik durumuna dair sınırlı bilgi vermektedir. Bununla birlikte Antik Dönemde Axylon olarak adlandırılmış bölgedeki yerleşim yerlerinden elde edilen mezar stelleri üzerinde yer alan tasvirler, bölge insanlarının çiftçilikle uğraştıklarını bütün açıklığıyla gözler önüne sermektedir. Öyle ki özellikle mezar stelleri üzerindeki bezeme unsurlarının büyük ekseriyeti zirai faaliyetlerle ilgili unsurlardır. Çift sürme sahneleri, saban, boyunduruk, buğday başağı, asma yaprağı, üzüm salkımı, yün sepeti, iğ, öreke bütün bölgede çok sık görülen figürlerdir. İşte bu çalışmada yazılı kaynaklar ve özellikle mezar stellerinin üzerlerindeki tasvirler yoluyla bölgenin Antik Dönem sosyal ve ekonomik hayatı ele alınmıştır.
MEZAR STELLERİ IŞIĞINDA ANTİK DÖNEMDE AXYLON BÖLGESİ’NİN SOSYAL VE EKONOMİK YAPISI
Keywords: Latin and Classical Greek Languages; Latince ve Klasik Yunan Dilleri